Perinatal outcomes in pregnant drug users attended at a specialized center - Antunes, Marcos Benatti; Demitto, Marcela de Oliveira; Padovani, Camila; Elias, Kelye Cristina de Moura; Miranda, Antonio Carlos Monteiro de; Pelloso, Sandra Marisa (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2018)
Objective: to analyze the perinatal repercussions of drug use by pregnant women treated in a high risk outpatient clinic. Method: a case-control study in which 920 medical records were evaluated in the period 2012-2013. The case group consisted of pregnant women who used licit/illicit drugs (41) and the control group of non-user pregnant women (82). Results: pregnant women using drugs presented increased risk for prematurity (RR = 2.64, p = 0.02), low birth weight (RR = 5.42, p = 0.01) and low one-minute Apgar score (RR = 2.97, p = 0.01). Conclusion: the results indicate that pregnant women who use drugs have unfavorable perinatal outcomes during gestation.